Cultural reappropriation in San Agustín - Ochoa-Jiménez, María Julia (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper reviews the cultural reappropriation concept as a state obligation, which comes together with the repatriation of cultural goods illicitly removed from their original sites. After observing how an indigenous group celebrated the Sun Day in the archaeological park San Agustin, we conclude that the cultural reappropriation concept can be understood in a more comprehensive manner.